2017
DOI: 10.1016/j.fuproc.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of micronized wood and energy-size relationship in wood comminution

Abstract: Mechanical milling demonstrates potential in the pretreatment arena to valorize lignocellulosic biomass because it eliminates chemicals and simplifies processing. The development of physical properties and energy consumption for generating micronized particles are key factors affecting potential use. This study investigated the effect of input moisture content, and feedstock particle size on developing physical characteristics of micronized particles and the resultant specific energy consumption in the milling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…The value of the calculated grinding parameter is proportional to the amount of energy consumed for grinding and the moisture content of the material. Similar results were obtained when studying the impact of moisture content and starting particle size on the specifi c energy consumption for the grinding of Douglas fi r [32]. The paper shows that the most suitable model for describing the correlation between specifi c energy consumption and changes in particle size changes is Rittinger's model.…”
Section: Discussionsupporting
confidence: 74%
“…The value of the calculated grinding parameter is proportional to the amount of energy consumed for grinding and the moisture content of the material. Similar results were obtained when studying the impact of moisture content and starting particle size on the specifi c energy consumption for the grinding of Douglas fi r [32]. The paper shows that the most suitable model for describing the correlation between specifi c energy consumption and changes in particle size changes is Rittinger's model.…”
Section: Discussionsupporting
confidence: 74%
“…It is similar in the case of specific comminution energy: an increase in disc angular velocity causes an increase in specific comminution energy, which demonstrates that the dynamics of increase in power consumption when changing the angular velocities is much greater than the dynamics of changes in the comminution efficiency. Details on the dependency of power consumption, efficiency, and specific comminution energy on process parameters such as the angular velocity of discs, batch feed speed, and the number of discs involved in grinding for a five-disc mill were presented in previous papers [ 16 , 19 , 24 ], and therefore they will not be discussed here in detail.…”
Section: Resultsmentioning
confidence: 99%
“…The tests conducted for ball mills [ 14 ], cylindrical mills [ 15 , 16 ], and hammer mills [ 1 , 17 ] showed that the particle size distribution curves vary depending on the process and design parameters of the mills used for grinding, e.g., the size of the grinding gap, rotational velocities, or the number of balls in ball mills. Furthermore, there is ongoing research to identify the relationship between the particle size of the ground product and the specific comminution energy for mills [ 18 , 19 , 20 , 21 ], which in a broader perspective should allow us to understand the comminution process to reduce the energy consumption and to optimise grinding machine designs.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is difficult to control the final size of ball-milled feedstocks. Nevertheless, equipment variables such as the rotational or vibrational frequency, ball diameter, and milling time can be used to achieve some level of control. , …”
Section: Lignocellulosic Biomass Size Reduction Equipmentmentioning
confidence: 99%
“…Nevertheless, equipment variables such as the rotational or vibrational frequency, ball diameter, and milling time can be used to achieve some level of control. 96,97 Rotary Bypass Shear Mill. The rotary bypass shear mill is relatively new lignocellulosic biomass size reduction equipment developed to address the limitations of conventional size reduction equipment, particularly the hammer mill.…”
Section: Equipmentmentioning
confidence: 99%